FAKTOR-FAKTOR PENYEBAB TIDAK TERCAPAINYA TUJUAN PEMIDANAAN LEMBAGA PEMASYARAKATAN DI INDONESIA (JURNAL HUKUM SEHASEN, 2015)
Many problems that happen in law institution at the moment prove that how weak of it running the laws especially of problem in law institution it self. The research uses normative law method by using comparative and conceptual approaches. The gathering data is law literature such as primary law matter, secondary and tertier. The analyze of law matter uses “content analysis”. Based on the result research and its analyze we come to the conclusion that: Firstly, the effect factors in the law institution on the treatment doesn’t touch the goal of treatment likely: law factor, the judgement’s factor, facility, society and culture factors. Keywords :  Cause, Not Proven, Punishment, Prison